Pencampuran Batu Kapur Dan Bottom Ash Sebagai Lapis Pondasi Kelas B Perkerasan Jalan Kabupaten Wakatobi - Masbahrin, Masbahrin; Muh. Magribi, La Ode; Rachmat, La Ode Musa (Universitas Sulawesi Tenggara, 2021)
Higway is an important infrastructure facility to support economic development in a region. The pavement construction of Wakatobi Regency is known to use materials imported form Palu City and Ambon City. In Wakatobi, there are actually quite a lot of local materials, such as send and limestone or limeston, but they cannot be used optimally. The puepose of this study wa to determine the characteristics of Komala limeston and the characteristics of bottom ash taken from the Nii Tanasa PLTU and how the ideal mixture composition between the two materials combined. The results showed that the characteristics of limestone/ limestone with the composition with the composition of broken stone 55% + 45% boottom ash, 50% broken stone + boottom ash 50% and 45% broken stone + 55% boottom ash obtained coarse agregate density = 1,491%, weight type of fine agregate (boottom ash) = 14,95% with each abrasion = 25,30% for testing the performance of an ideal mixture of Komala limeston and Nii Tanasa boottom ash with a composition of 55% broken stone + 45% boottom ash, CBR on γd Max. 61,76 % have met the specifications. Meanwhile the composition of 50% crushed stone + boottom ash 50% and 45% broken stone + 55% boottom ash does not meet the specifications of Bina Marga 2010. Copyright ©